Integrando humanos e dispositivos técnicos: o caso da coordenação das atividades entre a aciaria e o lingotamento contínuo - Rayra de Queiroz Flecha (2017)
This dissertation presents a research that develops itself on the demand of a large steel company that requested a study to automate an activity performed by operators. Given the first analyses made, it was clear that this activity could not be fully transferred to a system. The main issue for this demand is actually to identify how a decision support system could be designed to potentiate these operators´s activity. The essential objective is propose the requirements to design a technical device that is adherent to the reality of the work, resulting in an integrated system man-machine system. The methodology chosen to identify the set of rules and elements that could be transferred to a system that would execute this activity was the Ergonomic Analysis of Work (EAW). In the work environment of these operators were collected four cases, which served as a starting point to understand their real activity and the cognitive processes involved in their decision making. Based on what they performed at the moment of action of each of these cases, general and systematic observations, selfconfrontations and data validation meetings were carried out.Based on the results obtained from the data analyzes, we identified 22 activities that could be fully or partially executed by a system. These activities were classified into four natures of intervention: information availability, alarms, monitoring and simulation. This categorization allowed to promote discussions about how a computer support, conceived from the understanding of the operators course of action, can be more effective and result in its efficient use. More importantly, the issues of how activity is transformed the moment a system is inserted into it are addressed. This shows that the human being, even when he has a technical device to carry out his work, is not dispensable, but becomes a key element to achieve the expected objectives of the productive process.